The Impact of Job Satisfaction on Employee Turnover: An Applied Study at Nile Valley University and the University of Technology (The International Journal for Scientific Research, 2025)
This study aimed to analyze the relationship between job satisfaction and turnover rates in organizations. This study aimed to understand how factors such as the work environment, incentives, and salaries, relationships with colleagues and superiors, and work-life balance affect employee stability and loyalty. The results showed a strong, negative correlation between job satisfaction and employee turnover rates. Low satisfaction increases employee intention to seek other employment opportunities. Unfair wages or a lack of incentives were the primary reasons for employee turnover. The organizational environment and the relationship between management and colleagues were the main reasons for employee turnover. Most employees were dissatisfied, with few training opportunities available. Job satisfaction is not just a luxury; it is a strategic investment that reduces the costs associated with employee turnover.
Keywords: Job Satisfaction; Employee Turnover Rate; Nile Valley University; University of Technology